Experimental investigations on the wear behaviour of micro-EDM-fabricated textured tools during dry turning of Ti6Al4V. Issue 1 (4th January 2022) - Sahu, Tejanshu Sekhar; George, Allan; Kuriachen, Basil; Mathew, Jose; Dhanish, P.B.
Abstract : Purpose: This paper aims to focus on analysing the wear characteristics of tungsten carbide tools on which various micro patterns are fabricated to study its effect on the machinability of Ti-6Al-4V at dry turning conditions. Design/methodology/approach: Micro-patterns such as dimples, linear grooves and a novel combination of dimples and linear grooves were fabricated on rake faces of uncoated tools by micro-EDM process. Impact of these patterns on tool wear and chip morphology characteristics under dry machining conditions were analysed, and their performances were compared with the non-textured tool (NTT). Findings: Encouraging results in terms of minimal tool wear and favourable chip morphology characteristics were observed in case of all the textured tools, which demonstrated better tribological characteristics in contrast to NTT. The average flank wear was reduced by 43.5, 32 and 24.7% in dimple textured tool (DTT), linear textured tool (LTT) and hybrid textured tool (HTT), respectively, as compared to NTT. The average chip curl diameters measured for NTT, DTT, LTT, and HTT were observed to be 6.60, 3.51, 4.0 and 4.31 mm, respectively. Originality/value: The contribution of this work lies in fabricating innovative patterns using cost-effective micro-EDM process and analysing how the patterns, depending upon their dimensional area and wear debris accumulation characteristics, influence the machinability of Ti-6Al-4V in the absence of any lubrication mediums.